Autonomic modulation analysis in active and sedentary kidney transplanted recipients. (December 2015) - Moraes Dias, Carlos José; Anaisse Azoubel, Luana Monteiro; Araújo Costa, Herikson; Costa Maia, Ednei; Rodrigues, Bruno; Silva‐Filho, Antonio Carlos; Dias‐Filho, Carlos Alberto Alves; Claúdia Irigoyen, Maria; Leite, Richard D; de Oliveira Junior, Mário Sevilio; Mostarda, Cristiano Teixeira
Summary: Modulation of the autonomic nervous system on heart rate can be compromised in chronic kidney disease and may result in changes in the frequency and duration of the cardiac cycle. The aim of this study was to evaluate autonomic modulation in active and sedentary renal transplant recipients. Twenty renal‐transplanted individuals were analyzed at the Centro de Prevenção de Doenças Renais (Kidney Disease Education Centre), in the academic hospital of Universidade Federal do Maranhão, and were divided into the active group (AG) and the sedentary group (SG). The AG comprised of six men and four women (age 43.10 ± 13.02) and was in regular concurrent training intervention for 8 weeks, while the SG was composed of three men and seven women (age 36.8 ± 9.26). Analysis of heart rate (HR) variability in time and frequency domain demonstrated that HR mean values in the SG and AG were 787.32 ± 79.60 and 870 ± 106.66 ms, respectively. Differences were observed in the time domain and frequency domain. The total index of low frequency and high frequency showed no differences between the SG and AG. Biochemical variables presented significantly lower levels after 8 weeks of training. Higher heart rate variability in the time domain and greater vagal modulation was observed in the AG. The AG ad greater vagal modulation when compared to the SG, with removal of the sympathetic and increased parasympathetic in the behaviour was confirmed by sympatho‐vagal balance. The AG also presented significant improvements in the frequency domain.